2019
DOI: 10.1111/ced.14064
|View full text |Cite
|
Sign up to set email alerts
|

Functional symptoms in dermatology: Part 2

Abstract: Functional disorders within dermatology present as various constellations of skin symptoms, but without evidence of organic pathology. Examples can include mucocutaneous pain syndromes, functional pruritus, somatoform pain disorder and rarer entities, such as undifferentiated somatoform idiopathic anaphylaxis and multiple chemical sensitivity syndrome. These conditions can have a significant impact on a patient's quality of life, and can present challenges in communication, investigation and management. The ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…This can indicate that exposure to volatile organic compounds might be related to neurogenic inflammation and concomitant histamine-induced responses [ 52 , 67 ]. On the other hand, this symptom cluster has been viewed as a subtype of functional disorder [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can indicate that exposure to volatile organic compounds might be related to neurogenic inflammation and concomitant histamine-induced responses [ 52 , 67 ]. On the other hand, this symptom cluster has been viewed as a subtype of functional disorder [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Apremilast induces specific inhibition of phosphodiesterase-4, that inhibits T helper (Th)1and Th17, and decreases the release of inflammatory cytokines such as CXCL10. 5 In the case series by Kieffer et al 1 apremilast produced a sustained improvement in symptoms during the first 6 months of treatment, with a decrease in number and severity of lesions. However, in our study, we observed a lack of response in all of our five patients, four of whom had a follow-up time of > 6 months.…”
mentioning
confidence: 94%
“…Recently, the usefulness of apremilast was described in two papers. 1,2 In this study, we sought to assess the use of apremilast for HHD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It discussed the assessment and management of patients with a suspected functional dermatological disorder. 1 The authors suggested that an approach to managing vulvodynia could include starting with topical preparations such as capsaicin. We would like to share our experience of managing vulvodynia in our multidisciplinary vulval clinic, which has highlighted that the reported potential irritation with capsaicin is common.…”
mentioning
confidence: 99%